Age-Related Hearing Loss in Underprivileged Population of Pakistan (Medical Forum Monthly, 2024)
Objective: To determine the frequency and severity of age-related hearing loss.Study Design: Cross-sectional studyP0lace and Duration of Study: This study was conducted at the Department of ENT Head &Neck Surgery, Lahore Medical and Dental College, Ghurki Trust and Teaching Hospital Lahore from 1st January 2024 to 30th June 2024.Methods: Three hundred and eighty adults patients aged between 60-85 years, diagnosed with hearing loss were enrolled. Participants underwent otoscopy examination, tympanometry, and pure tone audiometry. All patients reporting with hearing loss, tinnitus, or vertigo were included. History of ear surgery, chronic discharge, impacted wax or ototoxic medications and noise exposure were excluded.Results: 15.7% of patients with ear-related symptoms had incidental findings of hearing loss.10.5% had mild, 28.9% had moderate, 25.4% had moderately severe, 31% had severe, 4.2% had profound in sensorineural hearing loss. 1.2% of cases had predominantly mild to moderate was found conductive hearing loss. 30.6% of cases were in moderate to severe ranges.71.3% had type A findings in mixed hearing loss. According other types, type As 0.7%, Ad 8.3%, B 10% and C 9.1%.Incidental findings were 15.7% of total, with non-incidental findings at 84.3%.Moderate and moderately severe hearing loss was the most common. Sensorineural hearing loss(SNHL) was prevalent with severe cases, while conductive hearing loss (CHL) was rare and generally mild of hearing loss severity. Overall, severe SNHL and mixed hearing loss were the most frequent types of hearing loss, with few cases of CHL.Conclusion: The high rates of moderate to severe sensorineural and mixed hearing loss in Pakistan's underprivileged population highlight the urgent need for early detection and better healthcare access to address age-related hearing loss.